Role of Innate T Cells in Anti-Bacterial Immunity - Gao, Yifang; Williams, Anthony P. (Frontiers in Immunology, 2015)
Innate T cells are a heterogeneous group of αβ and γδ T cells that respond rapidly (<2 hours) upon activation. These innate T cells also share a non MHC class I or II restriction requirement for antigen recognition. Three major populations within the innate T cell group are recognized, namely Invariant NKT cells (iNKT); Mucosal associated invariant T cells (MAIT) and gamma delta T cells. These cells recognize foreign/self-lipid presented by non-classical MHC molecules, such as CD1d, MR1 and CD1a. They are activated during the early stages of bacterial infection and act as a bridge between the innate and adaptive immune systems. In this review we focus on the functional properties of these 3 innate T cell populations and how they are purposed for antimicrobial defense. Furthermore we address the mechanisms through which their effector functions are targeted for bacterial control and compare this in human and murine systems. Lastly we speculate on future roles of these cell types in therapeutic settings such as vaccination.